Opening remarks - Kishko D.; Кішко, Д.; Кішко, Дмитро Іванович; Кішко, Д. І. (Одеса : НУ «ОЮА», 2026)
The foreword examines the current challenges and future prospects of forensic science in the context of the digital transformation of criminal justice. It emphasizes the changing nature of forensic objects, the growing importance of digital evidence, electronic documents, information and communication system data, and artificial intelligence technologies. The author highlights the need to combine technological innovation with scientifically validated methodologies, professional expertise, and strict adherence to procedural safeguards. Particular attention is paid to the development of interdisciplinary approaches, the enhancement of forensic support for criminal investigations, international professional cooperation, and the role of forensic science in documenting war crimes and ensuring reliable evidence in the digital era.
Kishko D. Opening remarks. Криміналістика майбутнього: цифрові інновації, штучний інтелект, глобальні виклики та загрози : збірник матеріалів міжнар. наук.–практ. конф. (м. Одеса, 5 черв. 2026 р.)=Criminalistics of the Future: Digital Innovations, Artificial Intelligence, Global Challenges and Threats: Proceedings of the International Scientific and Practical Conference (Odesa, 5 June 2026) / заг. ред. С. Ківалова, М. Аракеляна. Одеса : НУ «ОЮА», 2026. С. 46-47. URL: https://doi.org/10.32837/11300.33649
Keywords: forensic science; criminalistics; digital evidence; artificial intelligence; digital technologies; electronic documents; digital traces; interdisciplinary approach; war crimes; criminal justice; судова експертиза; криміналістика; цифрові докази; штучний інтелект; цифрові технології; електронні документи; цифрові сліди; міждисциплінарний підхід; воєнні злочини; кримінальне судочинство